Art Worlds in Situation: Old Methods for a (New) Anthropology of Popular Music and Dance in Migration - Aterianus-Owanga, Alice (My University, 2024)
The aim of this paper is to highlight how recent anthropological studies of musicians’ and dancers’ activities and networks in migration have attempted to theorize the links between the so-called ‘local’ and ‘global’ by both reviving older ethnographic methods and taking inspiration from recent theories and concepts in the anthropology of migration. It draws on the author’s research on the migration of Senegalese sabar dancers in Europe (mainly France and Switzerland), and on other anthropological studies developed recently about the worlds of music and dance in migration and transnational contexts. After briefly recalling the long history of the intertwining of migration studies and ethnomusicology, it focuses on two main tools that help to grasp the transnational connections and creations that emerge through music and dance and to overcome the simple dichotomy between the local and the global. These methods consist in analyses of ‘social worlds’ and ‘art worlds’ on the one hand and of ‘social situations’ on the other. It is shown how, using these tools, the anthropology of music and dance in migration can find relevant methodologies and epistemologies to overcome the local/global dichotomy and explain how ‘art worlds’ (Becker 2008 [1982]) are built into the interstices between the two scales.